2016
DOI: 10.21577/1984-6835.20160079
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study on the Collection and Incorporation of Cellulose Nanocrystals in Biodegradable Films

Abstract: Abstract:In recent years, several research groups have reported new techniques for forming nanocelulose from different natural sources and for the incorporation of these polymeric materials. The objective of this work was to technological prospecting mapping process to obtain nanocrystals, main sources and implementing them in biodegradable films. It was observed that the United States stands out as the largest holder of technology of interest.Keywords: Nanocellulosicas fibers; nanocellulose; patents; composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
2
4
0
1
Order By: Relevance
“…In this study, the CC fiber presented the highest concentration of cellulose and, consequently, presented the lowest L/D ratio for the nanocrystals obtained. The L/D ratio ranged from 32.19 to 40.86, being in agreement with other studies that presented values between 18.2 and 75.4 nm [13,79]. Some authors [11,80,81] found similar dimensions for the coconut shell.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the CC fiber presented the highest concentration of cellulose and, consequently, presented the lowest L/D ratio for the nanocrystals obtained. The L/D ratio ranged from 32.19 to 40.86, being in agreement with other studies that presented values between 18.2 and 75.4 nm [13,79]. Some authors [11,80,81] found similar dimensions for the coconut shell.…”
Section: Discussionsupporting
confidence: 90%
“…Oliveira [77] notes that the resulting nanoparticle dimensions depend on the cellulose source and the hydrolysis process. Smaller nanoparticle diameters may be associated with higher amounts of hemicellulose present in the fiber structure, which would limit the organization of cellulose chains [78,79]. In this study, the CC fiber presented the highest concentration of cellulose and, consequently, presented the lowest L/D ratio for the nanocrystals obtained.…”
Section: Discussionmentioning
confidence: 72%
“…A high brightness and transparency are valuable characteristics to the marketing industry, which seeks a good visual presentation of the products for the acceptance of the consumer. On the other hand, the protection against the incidence of light is necessary for the packaging of products that can deteriorate …”
Section: Resultsmentioning
confidence: 99%
“…The use of weak acids leads to cellulose fibers with low crystallinity and fibrous morphology as a result of the low dissociation constant of these acids [76]. Despite being a simple and fast isolation method, sulfuric acid hydrolysis has the advantage of yielding CNCs with higher crystallinity degree (over 90%) and also leads to the sulfate esterification of the CNCs surface, which enhances CNCs' phase stability in aqueous medium [79]. However, sulfate esterification decreases their thermal stability in the case of thermal treatments.…”
Section: Cellulose Nanocrystalsmentioning
confidence: 99%